GUT MICROBIOTA AND CARDIOVASCULAR RISK FACTORS. PART 2. GUT MICROBIOTA AND OBESITY - D. A. Kashtanova; O. N. Tkacheva; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2015)
The importance of adipose tissue is much greater than it has been expected. Adipose tissue is a large endocrine organ, value of which is difficult to overestimate. Its work influences a lot of metabolic disorders, cardiovascular pathology. Recently, there is active research on the relation of obesity and microbiota contents. It is studied depending on the food type, physical activity, and microbiota itself might influence the absorption of nutrients, permeability of the gut wall, and appetites. The article is focused on several mechanisms of interrelation of gut microbiota and obesity, on the results of last years studies.